The Role and Therapeutic Potential of Pyroptosis in Colorectal Cancer: A Review - Qing Fang; Yunhua Xu; Xiangwen Tan; Xiaofeng Wu; Shuxiang Li; Jinyi Yuan; Xiguang Chen; Qiulin Huang; Kai Fu; Shuai Xiao (Biomolecules, 2024)
Colorectal cancer (CRC) is one of the leading causes of cancer-related mortality worldwide. The unlimited proliferation of tumor cells is one of the key features resulting in the malignant development and progression of CRC. Consequently, understanding the potential proliferation and growth molecular mechanisms and developing effective therapeutic strategies have become key in CRC treatment. Pyroptosis is an emerging type of regulated cell death (RCD) that has a significant role in cells proliferation and growth. For the last few years, numerous studies have indicated a close correlation between pyroptosis and the occurrence, progression, and treatment of many malignancies, including CRC. The development of effective therapeutic strategies to inhibit tumor growth and proliferation has become a key area in CRC treatment. Thus, this review mainly summarized the different pyroptosis pathways and mechanisms, the anti-tumor (tumor suppressor) and protective roles of pyroptosis in CRC, and the clinical and prognostic value of pyroptosis in CRC, which may contribute to exploring new therapeutic strategies for CRC.